Factor V Leiden and Thermolabile Methylenetetrahydrofolate Reductase in Extreme Old Age - Rees, D C; Liu, Y T; Cox, M J; Elliott, P; Wainscoat, J S (Thrombosis and Haemostasis, 1997)
Both factor V Leiden and the C677T methylenetetrahydrofolate reductase (MTHFR) gene mutation are associated with premature vascular disease, and yet are found at surprisingly high allele frequencies in European populations, 2.7% and 35% respectively. We have investigated the prevalence of these mutations in 87 UK residents over the age of ninety, to look for any evidence of their association with premature death.Five factor V Leiden heterozygotes were found, giving an allele frequency of 2.9%, similar to that in the general UK population. The frequency of the thermolabile C677T MTHFR mutation was 36% with 11% homozygotes, again similar to that in the UK population; these genotypes are in Hardy-Weinberg equilibrium, suggesting that there is not strong selection against the homozygous state. One person was both heterozygous for factor V Leiden and homozygous for the C677T mutation. This study suggests that neither factor V Leiden nor thermolabile MTHFR are risk factors for premature death.